Designing marine protected area networks to address the impacts of climate change. Issue 7 (10th October 2008) - McLeod, Elizabeth; Salm, Rodney; Green, Alison; Almany, Jeanine
Abstract : Principles for designing marine protected area (MPA) networks that address social, economic, and biological criteria are well established in the scientific literature. Climate change represents a new and serious threat to marine ecosystems, but, to date, few studies have specifically considered how to design MPA networks to be resilient to this emerging threat. Here, we compile the best available information on MPA network design and supplement it with specific recommendations for building resilience into these networks. We provide guidance on size, spacing, shape, risk spreading (representation and replication), critical areas, connectivity, and maintaining ecosystem function to help MPA planners and managers design MPA networks that are more robust in the face of climate‐change impacts.